Improving Indonesian Language Learning Achievement Regarding Reading Ability Using The Make A Match Method For Class II MI Al Khoiriyah Students - Setiyawati, Setiyawati (Journal of Social Science and Economics, 2023)
The research with the title "Increasing Indonesian language learning achievement regarding reading skills using the make a match method for class II Mi al Khoiriyah students in the 2020/2021 academic year" is classroom action research. What was examined in this research was the application of learning using the make a match model to improve student learning outcomes. This research uses observation to determine the make a match learning process, observation to determine student learning outcomes. The make a match model in the learning process has 10 stages. Stage 1: 1 Teacher explains the learning objectives. Stage 2 The teacher determines the topic, namely the theme of reading about playing in my environment. stage 3 The teacher divides the students in the class into 3 groups. stage 4 The teacher prepares and distributes question cards for one group and answer cards for one group, stage 5 Each member of group 1 holds a question card and each member of group 2 holds an answer card. Stage 6 The teacher gives a sign ( whistle). Each group member moves to look for a partner (questions and answers). If it is found, give it to the assessment team. Stage 7. The teacher gives a signal (whistle). Each group member moves to look for a partner (questions and answers). If it is found, give it to the assessment team. Stage 8 Students who cannot match their cards with their friends' cards (cannot find the question card or answer card) will receive a punishment, which has been mutually agreed upon. Stage 9 The assessing group assesses whether the pairs of cards match. The assessment group explains the results of their assessment of the card pairs (questions and answers). Stage 10 The teacher together with the students make conclusions about the subject matter. This research is Classroom Action Research (PTK) with the spiral model from Kemmis and Taggart which consists of 2 action cycles. Each cycle consists of four stages including: planning, implementing, observing and reflecting. This research shows that student learning outcomes have improved after taking action. The percentage of students who had not completed decreased from cycle 1 to cycle 2 (72% to 0%). The percentage of students who completed increased from cycle 1 to cycle 2 (28% to 100%). The indicator of the success of this PTK is that this PTK is said to be successful if the percentage of students whose learning outcomes have been completed reaches at least 85%. And the table shows that the percentage of students whose grades are complete has reached 100%. So this PTK has been successful.